ANALYSIS OF FACTORS AFFECTED ON EFFICIENCY MILK FARMS - Jarka, Sławomir (Acta Scientiarum Polonorum. Oeconomia, 2007)
Milk production is an important source of income for more than 400 thousand farms in Poland. It constituted over 17% of agricultural market output in 2005. An increasing extent of cows breeding concentration has been noticed in Poland, especially on farms specialized in this field. A number of animals in one herd in countries of the Western Europe is from 20 to 60 cows but an average herd in Poland is about 4 cows. However, increasing proportion of farms, which are specializing in milk production, with large herds can be noticed. Conducted researches show that in a group of farms breeding from 10 to 50 cows, 80% of farms has enlarged their herds on average with 10 animals. An average number of herds was 28 cows on these farms. Researches were conducted on farms in Sośno commune in Sępolno poviat. It is typically agricultural commune, where 75% of area is agricultural land and an average farm is 18 ha. The basic goal set within the researches was to determine an extent of changes, which took place after Polish accession to the EU and also intensity of interest in property changes. In researched commune there was 25% of land owned by the Agricultural Property Agency (APA).